The Burnout amongst doctors of obstetrics and gynecology department during covid-19 pandemic: Burnout amongst doctors of obstetrics & gynecology department - Khansa Iqbal Ahmed, Saira Ahmed, Lubna Ejaz Kahloon, Humaira Noureen, Tallat Iftikhar, Humaira Bilqees (Journal of Rawalpindi Medical College, 2021)
Abstract : Burnout is a state of physical and mental exhaustion that results from long term involvement in work situations that are emotionally demanding. Doctors in emergency fields like obstetrics & gynecology of a tertiary care hospital, have to work vigilantly at odd times under immense pressure during long duty hours, thus are more likely to burnout, especially in the tedious time of COVID-19 pandemic. This study measured the burnout in doctors of the department of OB/GYN at RMU allied hospitals by using Questionnaire based on Copenhagen Inventory with addition of questions about PPE, COVID testing facility and family burnout. Results showed inadequate provision of PPE & Covid testing, fear of transmission of infection to family and friends, effect on care of elderly at home, relationship with partner and increased mood irritability. Personal burnout was 54, work related burnout 49.6, and patient related burnout was 37 There is significant family and personal burnout but still patient burnout is not present, showing high professionalism in our doctors. Facilitation in the form of reduced working hours, safer working environment, appreciation of work, financial incentives, social support and care of psychological well-being by cognitive behavioral therapy & counselling must be offered to the doctors of the department of obstetrics and gynecology.